Training curriculum needs for entrepreneurship literacy of higher education in society 5.0 - Babang Robandi; Wawan Setiawardani (Universitas Pendidikan Indonesia, 2025)
The Society 5.0 era requires a holistic integration of entrepreneurial literacy, striking a balance between technological competencies and humanistic values. However, higher education curricula remain fragmented, failing to address these needs comprehensively. This study aims to analyze the requirements for designing an entrepreneurship literacy training curriculum responsive to the challenges of Society 5.0 by employing a phenomenological method. In-depth interviews were conducted with five students to explore their experiences in three key areas: mastering disruptive technology, developing collaborative soft skills, and understanding digital ethics. Results indicate that students underutilize advanced digital marketing features (e.g., paid ads, Reels) despite familiarity with platforms like WhatsApp and Instagram. Collaborative efforts are hindered by low trust and ineffective partnership strategies, while awareness of digital ethics, particularly regarding consumer privacy and sustainability, remains limited. The study highlights the urgent need for curricula that systematically integrate disruptive technology, collaborative approaches, and digital ethics. These findings serve as a foundation for developing training modules tailored to students' real-world needs, fostering adaptive, collaborative, and ethical entrepreneurial competencies in the Society 5.0 era. Abstrak Era Society 5.0 menuntut integrasi holistik literasi kewirausahaan yang seimbang antara kompetensi teknologi dan nilai-nilai humanistik. Namun, kurikulum pendidikan tinggi masih terfragmentasi dan belum memenuhi kebutuhan ini secara komprehensif. Penelitian ini bertujuan untuk menganalisis kebutuhan dalam merancang kurikulum pelatihan literasi kewirausahaan yang responsif terhadap tantangan Society 5.0 dengan menggunakan metode fenomenologi, wawancara mendalam dilakukan terhadap lima mahasiswa untuk mengeksplorasi pengalaman mereka dalam tiga aspek utama yaitu penguasaan teknologi disruptif, pengembangan keterampilan kolaboratif, dan pemahaman etika digital. Hasil penelitian menunjukkan bahwa mahasiswa kurang memanfaatkan fitur pemasaran digital canggih (misalnya iklan berbayar, Reels) meskipun familiar dengan platform seperti WhatsApp dan Instagram. Upaya kolaborasi terhambat oleh rendahnya kepercayaan dan strategi kemitraan yang tidak efektif, sementara kesadaran akan etika digital, khususnya terkait privasi konsumen dan keberlanjutan, masih terbatas. Studi ini menggarisbawahi perlunya kurikulum yang secara sistematis mengintegrasikan teknologi disruptif, pendekatan kolaboratif, dan etika digital. Temuan ini menjadi landasan untuk mengembangkan modul pelatihan yang sesuai dengan kebutuhan nyata mahasiswa, guna membentuk kompetensi kewirausahaan yang adaptif, kolaboratif, dan beretika di era Society 5.0. Kata Kunci: fenomenologi; kurikulum pelatihan; literasi kewirausahaan; society 5.0